Implementation of the MSME Digitalization Policy Through the Markaz Application in Wonosobo Regency: Implementasi Kebijakan Digitalisasi UMKM melalui Aplikasi “Markaz UMKM” di Kabupaten Wonosobo - Anindita Sarsabila; Bachtiar Dwi Kurniawan (Jurnal Pemerintahan dan Politik, 2026)
Purpose – This study aims to identify the factors influencing the implementation process of digitalization policy through the "Markaz UMKM" application in Wonosobo Regency. Methodology – The research method employed is qualitative analysis, with primary data sources derived from in-depth interviews with two informants from the Wonosobo Chamber of Commerce and Industry (KADIN) and three informants from business actors using the application. This is supported by secondary data from credible sources. Findings – The results indicate a successful implementation of the digitalization policy through the "Markaz UMKM" application in Wonosobo Regency. Positive impacts were felt by business actors in utilizing digital technology for their business processes to widely promote local products. Socialization and training conducted by the Wonosobo Chamber of Commerce and Industry successfully enhanced business actors' understanding of digitalization and the application. However, a constraint faced is the lack of awareness among urban communities regarding digitalization. Practical Implications – Business actors are able to develop and widely introduce their products. Furthermore, there is a need for application development to facilitate the buying and selling process, as well as collaboration among stakeholders and related parties so that the "Markaz UMKM" application becomes more widely recognized and can assist business actors. Originality/Value – The novelty of this research lies in the use of Marilee S. Grindle's policy implementation theory and its focus on the factors influencing the implementation of digitalization.